Augmented Lateral Rectus Recession for Consecutive Exotropia. Issue 3 (3rd July 2021) - Nash, David; Brodsky, Michael C.
ABSTRACT: Purpose : To evaluate the efficacy of augmented bilateral lateral rectus recession in the treatment of consecutive exotropia. Methods : We retrospectively reviewed records of nine patients who underwent augmented bilateral lateral rectus recession for consecutive exotropia with minimal adduction deficits. Our normal surgical dosing tables for bilateral lateral rectus recession were augmented by adding 1.5–2 mm. All patients had been measured preoperatively using prism and alternate cover testing (PACT), except for one patient in whom Krimsky measurements were performed because of amblyopia. Surgery was deemed successful if postoperative alignment fell within a potential monofixation range of ±10 prism diopters (PD) by PACT at the final postoperative examination. Results : Eight out of nine patients (89%) had a successful outcome. One patient was surgically undercorrected. Despite successful realignment to a state of monofixation syndrome in most patients, there was no significant restoration of stereopsis following strabismus surgery. Conclusions : Surgical augmentation of bilateral lateral rectus recession standard dosing by 1.5–2 mm is efficacious for restoring binocular alignment for both distance and near fixation. This surgical approach may be preferable to bimedial advancements in patients with minimal preoperative adduction deficits who show no significant increase in exotropia during near fixation.